2003
DOI: 10.1128/ec.2.3.501-509.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Protozoan ParasiteEntamoeba histolyticaContains 20 Cysteine Protease Genes, of Which Only a Small Subset Is Expressed during In Vitro Cultivation

Abstract: Cysteine proteases are known to be important pathogenicity factors of the protozoan parasite Entamoeba histolytica. So far, a total of eight genes coding for cysteine proteases have been identified in E. histolytica, two of which are absent in the closely related nonpathogenic species E. dispar. However, present knowledge is restricted to enzymes expressed during in vitro cultivation of the parasite, which might represent only a subset of the entire repertoire. Taking advantage of the current E. histolytica ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 47 publications
6
121
1
3
Order By: Relevance
“…The genome is predicted to encode several hydrolases that might be involved in attacking host tissue (Denoeud et al, 2011), although tissue invasion by Blastocystis has never been observed in humans. The most likely possible effectors found in the Blastocystis genome are cysteine proteases, considering that these genes are also present in large numbers in the pathogenic protist Entamoeba histolytica (Bruchhaus et al, 2003). Nonetheless, these predictions all need further elucidation in the laboratory in order to determine whether they have any role in pathogenesis and disease and to prove that they are secreted.…”
Section: Blastocystis Nuclear Genomementioning
confidence: 99%
“…The genome is predicted to encode several hydrolases that might be involved in attacking host tissue (Denoeud et al, 2011), although tissue invasion by Blastocystis has never been observed in humans. The most likely possible effectors found in the Blastocystis genome are cysteine proteases, considering that these genes are also present in large numbers in the pathogenic protist Entamoeba histolytica (Bruchhaus et al, 2003). Nonetheless, these predictions all need further elucidation in the laboratory in order to determine whether they have any role in pathogenesis and disease and to prove that they are secreted.…”
Section: Blastocystis Nuclear Genomementioning
confidence: 99%
“…The CP-deficient trophozoites also failed to induce the intestinal epithelial cell production of the inflammatory cytokines IL-1β and IL-8 and caused significantly less intestinal inflammation and tissue damage (Zhang et al, 2000). More than twenty full-length CP genes have been identified to date in the E. histolytica genome but only about half of them have been found to be expressed in trophozoites cultured under axenic conditions (Bruchhaus et al, 2003;Tillack et al, 2006Tillack et al, , 2007. Four of the CPs (EhCP-1, EhCP-2, EhCP-3 and EhCP-5) have been purified and found to account for approximately 90 % of the total CP activity present in lysates of axenically cultured trophozoites (Scholze & Tannich, 1994;Bruchhaus et al, 1996Bruchhaus et al, , 2003Jacobs et al, 1998).…”
Section: Cysteine Proteinases (Cps)mentioning
confidence: 99%
“…More than twenty full-length CP genes have been identified to date in the E. histolytica genome but only about half of them have been found to be expressed in trophozoites cultured under axenic conditions (Bruchhaus et al, 2003;Tillack et al, 2006Tillack et al, , 2007. Four of the CPs (EhCP-1, EhCP-2, EhCP-3 and EhCP-5) have been purified and found to account for approximately 90 % of the total CP activity present in lysates of axenically cultured trophozoites (Scholze & Tannich, 1994;Bruchhaus et al, 1996Bruchhaus et al, , 2003Jacobs et al, 1998). EhCP-5 which has significant homology to cathepsin L appears to be of special importance for pathogenicity because it is the only CP that was found to be present on the surface of the trophozoite (Jacobs et al, 1998).…”
Section: Cysteine Proteinases (Cps)mentioning
confidence: 99%
“…Redundancy also characterizes many of the genes encoding suspected or proven E. histolytica virulence factors. New cysteine proteinase genes were identified (there are now at least 20), some of which contain putative transmembrane domains -which are lacking in the cathepsins of higher eukaryotes [2,3]. Three new amebapore genes were identified (bringing the total to six) and 30 homologs of a gene encoding the intermediate subunit of an E. histolytica surface lectin were identified.…”
Section: Repetition and Redundancymentioning
confidence: 99%
“…The issue of gene expression has been partially explored for the cysteine proteinase genes, in which it was observed that trophozoites in culture seem to express only eight of the 20 identified cysteine proteinase genes, with only six of the eight being expressed at significant levels [3]. It remains to be determined whether similar ratios exist for the other large gene families identified by the genome project.…”
Section: Repetition and Redundancymentioning
confidence: 99%